Place as Pedagogy: Toward Study Abroad for Social Change. (March 2018) - Pipitone, Jennifer M.
Background: Emergent bodies of literature have uncovered problematic trends in U.S. study abroad that reproduce hierarchies of power and colonialism, perpetuate views of an exotic cultural "other, " and privilege tourism over education.Purpose: This work responded to these problems by exploring ways of teaching and learning in study abroad that embrace the pedagogical power of place to foster awareness of the self in relation to other, cultivate relationality, and deconstruct the exotic.Methodology/Approach: Reflecting on two major findings from a longitudinal comparative case study with 19 students on short-term study abroad programs to Morocco and Bali, this article considers how educators can adapt the intentions and practices of their programs to embrace the pedagogical potential of place to foster the renegotiation of representations and heightened relationality.Findings/Conclusions: Findings indicate engagement with place was fundamental to the production of experiential learning space, mediated through pedagogies that engaged students with local rhythms, meanings, and histories; social interactions; and cultural tools that engaged students in alternative ways of knowing and being in the world before and during the trip.Implications: This article offers five epistemological commitments and several pedagogical strategies to guide future program development with an eye toward social change.